2014
DOI: 10.1039/c4cp03367a
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of C60 fullerene complexation with antibiotic doxorubicin

Abstract: The aim of this paper was to provide the physico-chemical characterization of a key process leading to amplification of the antitumor effect of antibiotic Doxorubicin (Dox) in vivo and in vitro and occurring at the molecular level through complexation with C60 fullerene. A wide range of physico-chemical tools was used such as UV/Vis and NMR spectroscopies, atomic force microscopy, isothermal titration calorimetry and zeta-potential methods. The unusual thermodynamic behavior of the complexation process was rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
45
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 30 publications
7
45
0
1
Order By: Relevance
“…This result may be interpreted as a consequence of existence of at least two statistically different entities in solution, which are the C 60 fullerene aggregates (the first maximum) and the complexes between the C 60 and doxorubicin molecules (the second maximum) . This result is in agreement with previous spectroscopic investigation of C 60 + doxorubicin interaction in water solution and provides independent confirmation to the fact of complexation .…”
Section: Resultssupporting
confidence: 91%
“…This result may be interpreted as a consequence of existence of at least two statistically different entities in solution, which are the C 60 fullerene aggregates (the first maximum) and the complexes between the C 60 and doxorubicin molecules (the second maximum) . This result is in agreement with previous spectroscopic investigation of C 60 + doxorubicin interaction in water solution and provides independent confirmation to the fact of complexation .…”
Section: Resultssupporting
confidence: 91%
“…Prylutskyy et al. reported a value of ‒28 mV. In contrast, some authors found different values; for instance, Brant et al.…”
Section: Resultsmentioning
confidence: 98%
“…In order to utilize transport properties of C 60 fullerene, as a rule, it has to be chemically modified by attachment to the drug itself or other compounds (Zakharian et al 2005;Liu et al 2010). However, recently the ability of pristine C60 fullerene dissolved in water solution (to be further referred to as C 60 FAS) to act as a carrier due to non-covalent complexation with drug was reported Prylutskyy et al 2014a). This fact is manifested in the marked enhancement of the anti-tumor effect of the antibiotic doxorubicin in vitro and in vivo in the presence of C 60 fullerene (Panchuk et al 2015;Prylutska et al 2014), and makes the development of new improved regimes of combined C 60 fullerene chemotherapy potentially possible.…”
Section: Introductionmentioning
confidence: 98%